Prostate-Specific Antigen Progression Predicts Overall Survival in Patients With Metastatic Prostate Cancer: Data from Southwest Oncology Group Trials 9346 (Intergroup Study 0162) and 9916 - (:unkn) unknown (AMER SOC CLINICAL ONCOLOGY, 2009)
Purpose Prostate-specific antigen progression (PSA-P) is an indicator of progression in hormone-sensitive (HS) and castration-resistant (CR) prostate cancer (PC). We evaluated different definitions of PSA-P as predictors of overall survival (OS). Patients and Methods A total of 1,078 patients with HSPC who were on hormones ( Southwest Oncology Group [SWOG] trial 9346 [S9346]) and 597 patients with CRPC who were treated with chemotherapy ( SWOG trial 9916 [S9916]) were eligible for this analysis. PSA-P definitions tested included the following: PSA Working Group, Prostate Cancer Working Group (PCWG 2008), and other definitions. A time-varying approach analyzed associations between PSA-P at any time and OS. A landmark analysis examined the relationship between PSA-P status at 7 months for S9346, or 3 months for S9916, and subsequent OS. Results In the time-varying analysis, both working groups definitions were strongly associated with OS (P < .001) in both study settings. In patients enrolled onto S9346, both definitions predicted a 2.4-fold increased risk of death (ROD) and a greater than four-fold increased ROD if PSA-P occurred in the first 7 months. In S9916, they predicted a 40% increase in ROD and a two-fold increase in ROD if PSA-P occurred at 3 months. In landmark analyses of patients on S9346 by using the PCWG 2008 definition of PSA-P, median subsequent OS was 10 months versus 44 months in patients who did or did not have PSA-P by 7 months, respectively; in S9916, data were 11 months versus 18 months for patients who did or did not have PSA-P by 3 months, respectively. Conclusion PSA-P, defined as an increase of >= 25% greater than the nadir and an absolute increase of at least 2 or 5 ng/mL, predicts OS in HSPC and CRPC and may be a suitable end point for phase II studies in these settings.
Keywords: CLINICAL-TRIALS; WORKING GROUP; RECOMMENDATIONS